Effective Strategies for Managing Household Finances to Improve Family Welfare - Diana, Septa; Abdul Hafizt Arkan; Aliyyah Dewi Azra; Nur Edy Kurniawan; Eky Pratiwi; Nurul Handayani; Putut Inda Malasari; Siti Nurhiqmah (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Effective household financial management strategies are crucial factors in creating economic stability and improving family welfare. This research seeks to explore the most efficient approaches for managing household finances to enhance sustainable family financial stability managing household finances to support sustainable family financial resilience. A qualitative methodology was employed, incorporating literature reviews and direct observations of families practicing financial discipline principles of families who apply the principle of financial discipline. The findings reveal four primary strategies that significantly impact successful household financial management main strategies that contribute significantly to the success of household financial management. Mature and realistic financial planning based on household income and needs. Financial control is carried out in a disciplined manner through periodic recording and evaluation of expenses. increasing financial literacy for all family members, including children, through education and open communication. Effective communication and harmonious cooperation among family members are essential in the financial decision-making process. The consistent application of these strategies has been shown to strengthen family economic resilience, reduce financial conflicts, and create a healthy and productive financial environment. Thus, strategic household financial management plays a crucial contribution in helping attain sustainable family well-being sustainable family welfare.